The Political Context of the Percent Black-Neighborhood Violence Link: A Multilevel Analysis. (7th February 2015) - Vélez, María B.; Lyons, Christopher J.; Santoro, Wayne A.
Abstract: A century of urban research has established that percentage black associates positively with violence at the neighborhood level. We extend traditional structural explanations for this association by drawing attention to the political contexts of cities that may influence the race-violence link. Drawing on insights from social movement and racial politics literatures, we contend that the relationship between percentage black and neighborhood violence will be attenuated in cities with greater black political opportunities and black mobilization. We examine this thesis using multilevel data from the National Neighborhood Crime Study that provide sociodemographic and violence data for census tracts nested within 87 large cities. We pair these data with city-level measures of black political opportunities and mobilization. Multilevel analyses reveal that the relationship between percentage black and violence varies substantially across cities, and that the average positive relationship often is attenuated, and reduced to statistical insignificance, in cities with favorable political contexts. We propose that the substantive and symbolic benefits set in motion by favorable political contexts lay the foundation for neighborhood organization against violence. Un siglo de investigación urbana ha establecido que el porcentaje de población negra está asociado con la existencia de violencia en los vecindarios. Este estudio busca ampliar las explicaciones estructurales tradicionales que se han establecido para entender la relación entre raza y violencia y pone su atención en los contextos políticos. Sobre la base de la literatura de movimientos sociales y política racial, el artículo sostiene que la relación entre el porcentaje de población negra y la violencia en la vecindad se atenúa en las ciudades con mayores oportunidades políticas para la población negra y donde hay mayor movilización de esta población. En nuestro análisis utilizamos la base de datos de multinivel del Estudio Nacional de Crimen en Vecindades (National Neighborhood Crime Study) que nos proporciona datos socio-demográficos y de violencia en secciones demarcadas en el censo poblacional en 87 ciudades grandes. El análisis multinivel demostró que la relación entre el porcentaje de población negra y la existencia de violencia vecinal varía sustancialmente entre ciudades y que la relación positiva se atenúa y se vuelve estadísticamente insignificante en ciudades con contextos políticos favorables. Proponemos que los beneficios sustantivos y simbólicos puestos en marcha por contextos políticos favorables forman la base para la organización vecinal contra la violencia.